Tuning the properties of regenerated cellulose: Effects of polarity and water solubility of the coagulation medium. (15th May 2020) - From, Malin; Larsson, Per Tomas; Andreasson, Bo; Medronho, Bruno; Svanedal, Ida; Edlund, Håkan; Norgren, Magnus
Graphical abstract: Highlights: Wood cellulose was dissolved in cold aqueous alkali/urea and regenerated in alcohols and esters. Dry material was investigated regarding crystallinity, and various other material properties. Cellulose crystallinity depends on regeneration liquids water solubility rather than polarity. Various other material properties were dependant on cellulose crystallinity. A roadmap to fine-tune the final properties depending on requirements are provided. Abstract: In this study, the effect of different alcohols and esters as a coagulation medium in the regeneration of cellulose dissolved in an aqueous LiOH-urea-based solvent was thoroughly investigated using various methods such as solid state NMR, X-ray diffraction, water contact angle, oxygen gas permeability, mechanical testing, and scanning electron microscopy. It was observed that several material properties of the regenerated cellulose films follow trends that correlate to the degree of cellulose II crystallinity, which is determined to be set by the miscibility of the coagulant medium (nonsolvent) and the aqueous alkali cellulose solvent rather than the nonsolvents' polarity. This article provides an insight, thus creating a possibility to carefully tune and control the cellulose material properties when tailor-made for different applications.